First Attack and Clinical Presentation of Hemiplegic Migraine in Pediatric Age: A Multicenter Retrospective Study and Literature Review - Toldo, Irene; Brunello, Francesco; Morao, Veronica; Perissinotto, Egle; Valeriani, Massimiliano; Pruna, Dario; Tozzi, Elisabetta; Moscano, Filomena; Farello, Giovanni; Frusciante, Roberto; Carotenuto, Marco; Lisotto, Carlo; et al. (Frontiers in Neurology, 2019)
Background: Data on clinical presentation of Hemiplegic Migraine (HM) are quite limited in the literature, particularly in the pediatric age. The aim of the present study is to describe in detail the phenotypic features at onset and during the first years of disease of sporadic (SHM) and familial (FHM) pediatric hemiplegic migraine and to review the pertinent literature. Results: Retrospective study of a cohort of children and adolescents diagnosed with hemiplegic migraine, recruited from 11 Italian specialized Juvenile Headache Centers. 46 cases (24 females) were collected and divided in two subgroups: 32 SHM (16 females), 14 FHM (8 females). Mean age at onset was 10.5y + 3.8y (range: 2-16y). Mean duration of motor aura was 3.5 hours (range: 5 minutes - 48 hours). SHM cases experienced more prolonged attacks than FHM cases, with significantly longer duration of both motor aura and of total HM attack. Sensory (65%) and basilar-type auras (63%) were frequently associated to the motor aura, without significant differences between SHM and FHM. At follow-up (mean duration 4.4 years) the mean frequency of attacks was 2.2 per year in the first year after disease onset, higher in FHM than in SHM cases (3.9 vs 1.5 per year, respectively). A literature review retrieved 7 studies, all but one were based on mixed adults and children cohorts. Conclusions: This study represents the first Italian pediatric series of HM ever reported, including both FHM and SHM patients. Our cohort highlights that in the pediatric HM has an heterogeneous clinical onset. Children present fewer non-motor auras as compared to adults and in some cases the first attack is preceded by transient neurological signs and symptoms in early childhood. In SHM cases, attacks were less frequent but more severe and prolonged, while FHM patients had less intense but more frequent attacks and a longer phase of active disease. Differently from previous studies, the majority of our cases, even with early onset and severe attacks, had a favorable clinical evolution.